(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study investigates the creation and analysis of MnO₂ nanoparticles utilizing green chemistry techniques. To ensure the future viability of nanotechnology, it is critical to select environmentally friendly materials and techniques. A greener method of synthesis is developed by substituting natural sources for synthetic ones and using plant extracts to reduce and stabilize the reactants. MnO₂ nanoparticles are investigated using a variety of analytical procedures, including X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray fluorescence (XRF), and ultraviolet-visible (UV-visible) spectroscopy. Catalysis, energy storage, and biological applications are among the potential uses for the produced MnO₂ nanoparticles; the results reveal that the nanoparticles’ size and form may be controlled. The green synthesis approach offers an ecologically friendly and scalable way to produce MnO₂ nanoparticles, which contributes to the advancement of sustainable nanotechnology.